Common themes in antimicrobial and anticancer drug resistance - Chifiriuc, Mariana Carmen; Filip, Roxana; Constantin, Marian; Pircalabioru, Gratiela Gradisteanu; Bleotu, Coralia; Burlibasa, Liliana; Ionica, Elena; Corcionivoschi, Nicolae; Mihaescu, Grigore (Frontiers in Microbiology, 2022)
Antimicrobial and anticancer drug resistance represent two of the main global challenges for the public health, requiring immediate practical solutions. In line with this, we need a better understanding of the origins of drug resistance in prokaryotic and eukaryotic cells and the evolutionary processes leading to the occurrence of adaptive phenotypes in response to the selective pressure of therapeutic agents. The purpose of this paper is to present some of the analogies between the antimicrobial and anticancer drug resistance. Antimicrobial and anticancer drugs share common targets and mechanisms of action as well as similar mechanisms of resistance (e.g., increased drug efflux, drug inactivation, target alteration, persister cells’ selection, protection of bacterial communities/malignant tissue by an extracellular matrix etc.). Both individual and collective stress responses triggered by the chemotherapeutic agent involving complex intercellular communication processes, as well as with the surrounding microenvironment, will be considered. The common themes in antimicrobial and anticancer drug resistance recommend the utility of bacterial experimental models for unravelling the mechanisms that facilitate the evolution and adaptation of malignant cells to antineoplastic drugs.